A bibliometric analysis of environmental behavior (1974–2024): evolution of research hotspots and trends - Wang, Shanshan; Liu, Gangtian; Ma, Jun; Li, Hongyu; Li, Wenao; Bu, Huijie; Chen, Peng; Song, Peng; Chen, Qiaoxue (Frontiers in Psychology, 2025)
In recent years, environmental behavior has emerged as a crucial research direction for achieving sustainable development. Promoting environmental awareness and related practices can effectively reduce pollution, protect ecosystems, and enhance human well-being. A systematic understanding of research hotspots and evolutionary trends in this field holds significant theoretical and practical value. This study employed bibliometric methods and utilized ScientoPy and VOSviewer analysis tools to conduct a systematic and multi-dimensional analysis of 6,524 articles on environmental behavior published in the Web of Science and Scopus databases from 1974 to 2024. The findings show that the volume of literature on environmental behavior has grown rapidly, confirming its interdisciplinary and global nature. Diachronic clustering analysis identified three distinct evolutionary stages. China ranked first and the United States second in terms of the total number of publications. Current emerging hotspots with the fastest growth include “green human resource management” and “environmental awareness.” Meanwhile, “pro-environmental behavior,” “sustainability,” “climate change,” and “place attachment” remain consistently high-potential research themes. This study comprehensively reveals the historical evolution and shifting hotspots in environmental behavior research over the past 50 years. The findings provide strong evidence and clear directions for scholars, policymakers, and practitioners.